MITIGASI KEKUATAN DAYA TAWAR PEMASOK PADA PERUSAHAAN CONSUMER FINANCE: SUATU STUDI PUSTAKA - ,; ,; , (LUCRUM : Jurnal Bisnis Terapan; Vol 4 No 2 (2024): LUCRUM : Jurnal Bisnis Terapan, 2024)
Supplier bargaining power is one of the threats for consumer finance companies in Indonesia to gain sustainable competitive advantage. One consequence of the high bargaining power of suppliers can reduce the company's sales and income from financing consumers. Previous research generally still discusses from a supplier perspective which is less relevant to the conditions of consumer finance companies. Therefore, this research will discuss theoretical insights regarding buyer and supplier relationships from the buyer's perspective. This study adopts Social Exchange Theory, Resource Based Theory and Transaction Cost Theory and proposes a model of mitigating supplier bargaining power by increasing supplier involvement, increasing trust and collaborating. Keywords: suppliers, social exchange theory, resource-based theory, transaction cost theory, information sharing